Decellularized Ear Tissues as Scaffolds for Stem Cell Differentiation - Santi, Peter A. (Springer-Verlag, 2012)
Permanent sensorineural hearing loss is a major medical problem and is due to the loss of hair cells and subsequently spiral ganglion neurons in the cochlea. Since these cells lack the capacity of renewal in mammals, their regeneration would be an optimal solution to reverse hearing loss. In other tissues, decellularized extracellular matrix (ECM) has been used as a mechanical and biochemical scaffold for the induction of stem and other cells toward a target tissue phenotype. Such induced cells have been used for tissue and organ transplants in preclinical animal and human clinical applications. This paper reports for the first time the decellularization of the cochlea and identification of remaining laminin and collagen type IV as a first step in preparing an ECM scaffold for directing stem cells toward an auditory lineage. Fresh ear tissues were removed from euthanized mice, a rat and a human and processed for decellularization using two different detergent extraction methods. Cochleas were imaged with scanning thin-sheet laser imaging microscopy (sTSLIM) and brightfield microscopy. Detergent treatment of fresh tissue removed all cells as evidenced by lack of H&E and DNA staining of the membranous labyrinth while preserving components of the ECM. The organ of Corti was completely removed, as were spiral ganglion neurons, which appeared as hollow sheaths and tubes of basal lamina (BL) material. Cells of the stria vascularis were removed and its only vestige left was its laterally linking network of capillary BL that appeared to “float” in the endolymphatic space. Laminin and type IV collagen were detected in the ECM after decellularization and were localized in vascular, neural and epithelial BL. Further work is necessary to attempt to seed neural and other stem cells into the decellularized ECM to hopefully induce differentiation and subsequent in vivo engraftment into damaged cochleas. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10162-012-0355-y contains supplementary material, which is available to authorized users.